Determinants of Vietnam’s Potential Trade: A Case Study of Agricultural Exports to the European Union - Linh, Pham Hoang; Doanh, Nguyen Khanh; Quynh, Nguyen Ngoc (Asian Journal of Agriculture and Rural Development, 2019)
This study aims at quantifying the determinants of Vietnam’s potential exports to the EU, taking agricultural commodities as a case study. In order to achieve this, we employed a stochastic frontier analysis to estimate Vietnam’s potential agricultural exports, and a system GMM approach to analyze the determinants of the estimated potential agricultural exports of Vietnam. The results showed that Vietnam’s potential agricultural exports to the EU have been high and on an upward trend. In addition, factors such as financial market development, trade freedom, technological readiness, and labor freedom have positive impacts on Vietnam’s potential agricultural exports to the EU. Measures to improve the financial market development, remove trade barriers, increase technological capability, and promote labour freedom are strongly suggested in order to enable Vietnam’s agricultural exports to attain its maximum level.